Narodowe Odrodzenie Polski. Oblicze ideowe nacjonalistycznej partii politycznej - Dawidowicz, Aneta (Polityka i Społeczeństwo, 2021)
Within the views of the National Rebirth of Poland, critical judgements and the questioning of the existing socio-political order have prevailed. The liberal democratic system has been rejected, to be replaced by a regime in which all social norms are in accordance with Christian values. Both the area of economic and social, as well as political, life are to be shaped according to principles stemming from Christianity and Catholicism. The NOP propounds the view that in the independent Polish state there should be no room for any forces seeking to destroy national sovereignty in terms of internal relations, and the state in terms of external relations.